SOME DISADVANTAGES OF CENTRALIZED ONLINE TESTING - Lyubov M. Bukhman; Nikolay S. Bukhman (Высшее образование в России)
The mathematical model of centralized testing on the base of the Internet FEPO is described. It is shown that the test results depend not only on the level of students preparation, but also on the number of didactic units in the training course. The authors draw a conclusion of non-optimality of the system of Internet-based testing and substantiate the need to move away from the requirements of mastering all didactic course units.